59. CURRENT STATUS OF QUALITY OF LIFE MANAGEMENT OF CANCER PATIENTS AT TIEN GIANG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of quality of life management for cancer patients at Tien Giang General HospitalMaterials and methods: A cross-sectional descriptive study; surveying cancer patients diagnosed at any stage, aged over 18, receiving inpatient or outpatient treatment at the Oncology Department, Tien Giang General Hospital, from March 2025 to June 2025.Results: Among the 128 participants, more than 50% rated their quality of life and health at a low level, and 72% frequently experienced negative psychological states. The mean quality of life score (QOL) was 2.75 (43.75/100), highest in the psychological domain (56.71) and lowest in the physical domain (34.46). Patients in stages I–II were 4.17 times more likely to achieve a QOL score ≥3 compared to those in stages III–IV (p < 0.001).Conclusion: Appropriate solutions are needed to improve the effectiveness of quality of life management for cancer patients at Tien Giang General Hospital from 2025 to 2027.